Freestanding flexible polymer films based on bridging of two EDOT units with functionalized chains for use in long-term-stable supercapacitors. (6th March 2018) - Ye, Guo; Zhou, Qianjie; Li, Danqin; Zuo, Yinxiu; Duan, Xuemin; Zhou, Weiqiang; Xu, Jingkun
Abstract : Freestanding flexible films were prepared by cross-linking two EDOT unit with fictionalized flexible chains, the application of these films in supercapacitors showed excellent cycling life. Abstract : Freestanding flexible capacitive materials are ideal for use in bendable electronic devices. However, it is difficult to prepare pure PEDOT films in a freestanding state by chemical and electrochemical methods. Here, we used a simple strategy of introducing alkoxy, ether, ester, and amide chains for bridging two EDOT units to form precursors, which could then be electrodeposited readily to produce freestanding and flexible films. The precursor with the amide group was suitable for obtaining higher-quality films with improved thermal stability, mechanical properties, and capacitive performance. In addition, the asymmetric PBEDTA//PEDOT capacitors exhibited a capacitance retention rate of 98.5% after 5000 cycles, which is higher than those of PBEDTH//PEDOT (92.7%), PBEDTG//PEDOT (80.5%), and PBEDTE//PEDOT (86.8%) capacitors. This result indicates that the polymer films and, in particular, the PBEDTA films, are suitable for use in flexible supercapacitors.